Cangma Huadu granules attenuate H1N1 virus-induced severe lung injury correlated with repressed apoptosis and altered gut microbiome - Liu, Mingjiang; Liu, Tengwen; Wang, Xuerui; Yu, Chenglong; Qin, Tao; Li, Jingui; Zhang, Mina; Li, Zhenxuan; Cui, Xuran; Xu, Xiaolong; Liu, Qingquan (Frontiers in Microbiology, 2022)
Severe influenza A virus infection leads to overwhelming inflammatory responses and cellular apoptosis, which causes lung injury and contributes to high mortality and morbidity. The gut microbiome altered in response to the infection might influence the disease progression and the treatment outcome. Cangma Huadu (CMHD) granules, an in-hospital preparation of traditional Chinese medicine, have been shown as favorable in the clinical treatment of influenza. However, the effects and mechanisms of CMHD granules on severe influenza pneumonia and its mechanisms are not well known. In this study, a lethal influenza A (H1N1) A/Puerto Rico/8/34 virus (PR8) infection mice model was established, and the 16S ribosomal RNA (16S rRNA) V3-V4 region sequencing of the intestinal microbiome was conducted. We revealed that oral administration of CMHD granules protects mice against higher mortality, enhanced weight loss, overwhelmed interferon-γ concentration, lung viral titers, and severe lung pathological injury in PR8 infected mice. CMHD granules administration down-regulated the levels of interleukin (IL)-1β, tumor necrosis factor-α, and malondialdehyde, while up-regulated the levels of IL-10, superoxide dismutase, and glutathione peroxidase. Subsequently, it decreased the protein ratio of B-cell lymphoma-2 /Bcl-2-associated X, and the expression of cleaved caspase-3. The diversity and compositions of the gut microbial was altered profoundly after CMHD granules administration in PR8 infected mice. A higher abundance of Bifidobacterium, Parasutterella, Bacteroides, and Faecalibaculum was observed in the CMHD group, and a higher abundance of Lactobacillus and Turicibacter was observed in the positive drug Ribavirin group. The linear discriminant analysis effect size also revealed a higher proportion of Bacteroides and Bifidobacterium_pseudolongum characterized the CMHD group. These results demonstrated that CMHD granules, as a promising strategy for managing severe influenza, attenuate severe lung damage via reducing viral titer, inflammatory responses, and oxidative stress. The mechanisms are involved in repressed Bcl-2-regulated apoptosis and altered composition and diversity of the gut microbiome.